2021
DOI: 10.20944/preprints202112.0499.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Missing Limb: Including Impacts of Biomass Extraction on Forest Carbon Stocks in GHG Balances of Wood Use

Abstract: The global carbon neutrality challenge places a spotlight on forests as carbon sinks. However, greenhouse gas (GHG) balances of wood for material and energy use often reveal GHG emission savings in comparison with a non-wood reference. Is it thus better to increase wood production and use, or to conserve and expand the carbon stock in forests? GHG balances of wood products mostly ignore the dynamics of carbon storage in forests, which can be expressed as the carbon storage balance in forests (CSBF). For German… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Examples of such may be wood efficiently used for construction and bioenergy employed with carbon capture and storage (Soimakallio et al, 2021). Fehrenbach et al (2021) demonstrated in a case study for Germany that including CBI in GHG balances is relevant for climate policy. They found the effectiveness of GHG mitigation options involving wood use to be considerably reduced when accounting for the impacts of tree harvest on carbon stocks in forests assuming a CBI value of 0.25-1.15 t CO 2 /m 3 (~0.34-1.57 t C /t C with conversion factor of 0.2 t C /m 3 ) wood under German conditions.…”
Section: Putting Cbi Into Contextmentioning
confidence: 99%
“…Examples of such may be wood efficiently used for construction and bioenergy employed with carbon capture and storage (Soimakallio et al, 2021). Fehrenbach et al (2021) demonstrated in a case study for Germany that including CBI in GHG balances is relevant for climate policy. They found the effectiveness of GHG mitigation options involving wood use to be considerably reduced when accounting for the impacts of tree harvest on carbon stocks in forests assuming a CBI value of 0.25-1.15 t CO 2 /m 3 (~0.34-1.57 t C /t C with conversion factor of 0.2 t C /m 3 ) wood under German conditions.…”
Section: Putting Cbi Into Contextmentioning
confidence: 99%
“…Fehrenbach et al [29] demonstrated in a case study for Germany that including CBI in GHG balances is relevant for climate policy. They found the effectiveness of GHG mitigation options involving wood use to be considerably reduced when accounting for impacts of roundwood removals on carbon stocks in forests assuming a CBI value of 0.25 to 1.15 t CO2/m³ wood under German conditions.…”
Section: Putting Cbi In Contextmentioning
confidence: 99%
“…Consider how informative a CBI value, or the discussed range of ~0.34 to 1.57 tC/tC (Fehrenbach et al 2021), is as such, without information that the lower value was actually caused by a series of storms and drought that reduced both C and H in Germany. The likely existence of similar or opposite (+ΔC/+ΔH) cases argues against the use of filtered average CBIs.…”
mentioning
confidence: 99%